Impact of the COVID-19 pandemic on the kidney community: lessons learned and future directions - Geetha, Duvuru; Kronbichler, Andreas; Rutter, Megan; Bajpai, Divya; Menez, Steven; Weissenbacher, Annemarie; Anand, Shuchi; Lin, Eugene; Carlson, Nicholas; Sozio, Stephen; Fowler, Kevin; Bignall, Ray; et al. (Nature reviews. Nephrology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has disproportionately affected patients with kidney disease, causing significant challenges in disease management, kidney research and trainee education. For patients, increased infection risk and disease severity, often complicated by acute kidney injury, have contributed to high mortality. Clinicians were faced with high clinical demands, resource shortages and novel ethical dilemmas in providing patient care. In this review, we address the impact of COVID-19 on the entire spectrum of kidney care, including acute kidney injury, chronic kidney disease, dialysis and transplantation, trainee education, disparities in health care, changes in health care policies, moral distress and the patient perspective. Based on current evidence, we provide a framework for the management and support of patients with kidney disease, infection mitigation strategies, resource allocation and support systems for the nephrology workforce.